The implementation of digital-based accounting for fraud prevention at PNM Mekaar Syariah - Ramadhan, Gamadi; Suryani, Pesi; Lumban Gaol, Lasando (Institute of Computer Science (IOCS), 2024)
The 2019 Fraud Survey in Indonesia published the three biggest types of fraud occurring in the country, including corruption at 64.4%, misuse of state or company assets at 28.9%, and financial reporting fraud at 6.7%. PNM, as a company operating in the financial sector, is also vulnerable to fraud. Based on data from the Anti-Fraud Strategy Implementation Report of PNM 2022 published on the Indonesia Stock Exchange, it is known that the Mekaar service experienced 6,163 cases of fraud. This situation prompted PNM to undergo transformation in transaction recording processes using digital-based accounting. Considering this phenomenon, researchers were interested in analyzing the impact of implementing digital-based accounting on fraud prevention at PNM Mekaar Syariah. This research method employs a simple linear regression analysis model with the assistance of SPSS V.27 software. The data collection process involved questionnaires directed at Back Office employees and Finance Administration Officers at PNM Mekaar Syariah. From the analysis conducted on fifty samples, it is found that the implementation of digital-based accounting has a positive and significant impact on fraud prevention at PNM Mekaar Syariah.